The impacts of permanent food production park programon the participants’ knowledge, attitude, practice and income: a case study in Tawau, Sabah - Masni Mustamin; Abdul Rahim Awang; Assis Kamu (e-VIBS, Faculty of Science and Natural Resources, 2020)
Permanent Food Production Park program (or in Malay called as program Taman Kekal Pengeluaran Makanan, TKPM) is a strategy under Third National Agricultural Policy (DPN3). Tawau TKPM was started in 2008 with financial provision from the Federal Government. The project site was allocated by the Sabah State Government. The total area of the project was 92.3 hectares and divided into 59 lots, planted with various food crops. Currently, there are 43 entrepreneurs or participants involve in the project. The main purpose of this study was to identify the impacts of the implementation of Tawau TKPM on the knowledge, attitude, practices and income of the participants. The data for the study consisted of primary and secondary data. The primary data were obtained through questionnaire, while the secondary data were obtained from the records and reports published by the Department of Agriculture Sabah. All of the participants in the TKPM project in Tawau were selected as the respondents. The results of the Pearson’s chi-square test revealed that The TKPM project has certainly given a significant impact to the participants’ knowledge, attitude, and practices toward the good agricultural practices. The project at some extent has also successfully improved the participants’ income. The study also found that the TKPM project requires certain duration of participation to be effective since the participants are dealing with different types of food crops. The findings of the study can be used as a reference to the authority to enhance the effectiveness of this project as well as other similar projects if to be implemented in the state in the future.